Impact of Economic Instability on The Arabic Teachers' Productivity on Lessons Delivery in Higher Islamic Schools in Nigeria: Impact of Economic Instability on The Arabic Teachers' Productivity on Lessons Delivery in Higher Islamic Schools in Nigeria - Ahmad Garba; Iskandi; Dody Irawan; Anis Shalatin Simon; Suharia Sarif (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2026)
This research, titled "The Impact of Economic Instability on the Productivity of Arabic Language Teachers in Islamic Secondary Schools in Adamawa State, Nigeria," examines how economic instability affects the productivity of Arabic language teachers in some selected Islamic secondary schools in Adamawa State. It identifies gaps in timely salary payments, resources, and motivation. The research highlights how financial instability threatens teachers' basic needs, their perceptions of fairness, and their ability to perform optimally in the classroom. A correlational survey was conducted among 200 teachers, where 100 teachers were selected as sample, using instrument focusing on salary delays and resource shortages as factors that impede teacher motivation, teaching quality, and their overall productivity. The results show strong, significant negative correlations statistically, indicating that salary delays are a major factor which reduces teachers' motivation, weakens teaching quality, and leads to decreased productivity among teachers in Islamic schools. The research concludes that economic instability negatively affects Islamic secondary school teachers, reducing their motivation to teach and diminishing their enthusiasm to teaching profession. The study recommended that the government adopts a system that ensures timely payment of salaries for teachers in Islamic secondary schools, in addition to providing financial incentives for workshops or allowances or performance bonuses for teachers working in rural schools with limited resources.